Testing central auditory processing abilities in older adults with and without dementia using the consonant-vowel dichotic listening task - Littlejohn, Jenna; Blackburn, Daniel J.; Venneri, Annalena (Frontiers in Dementia, 2023)
Background: Hearing loss and dementia are linked, although the roles of peripheral and central auditory dysfunction are not well defined. Many behavioural measures of hearing are confounded by the overlapping cognitive functions required to perform the tests. Objective: To collect pilot data to identify how central auditory function, measured using a dichotic listening test that indexes both auditory and cognitive components under different attentional conditions, differs among people with mild cognitive impairment (MCI), dementia and controls, and how performance relates to neuropsychological results. Method: Fifty-eight participants (17 MCI, 11 dementia and 30 controls) undertook hearing screening, the Bergen consonant-vowel dichotic listening paradigm, and a short battery of neuropsychological tests chosen to index attention and executive control. Dichotic listening was assessed under three attentional conditions (non-forced, forced right ear and forced left) amongst older adults with normal cognitive function, MCI and dementia. Results: We report two main findings: (a) The expected right ear advantage under non-forced conditions, was seen in controls and patients with dementia but not in people with MCI, who showed equal numbers of correct responses from both ears (i.e. a lack of asymmetry); (b) Performance under forced attentional conditions was significantly associated with disease progression (i.e. control > MCI > dementia) and performance on the cognitive tasks. Conclusion: The reduction in asymmetry on dichotic listening tasks may be a marker of MCI and reflect underlying compensatory mechanisms. Use of this test could aid stratification of patients with memory disorders. Whether abnormalities could predict dementia onset needs longitudinal investigation in a larger sample.